Cooperative environments bolster feelings of autonomy in dyads, teams, and organizations - Valentino E. Chai; Nir Halevy (Proceedings of the National Academy of Sciences, 2026)
Autonomy promotes important psychological outcomes. Although cooperation and competition are the building blocks of social interactions, little is known about how they shape feelings of autonomy in dyads, teams, and work organizations. We hypothesize that cooperation liberates relative to competition and situations that are neither cooperative nor competitive. We theorize that this effect emerges because cooperation facilitates social support and psychological safety, whereas competition promotes social threat and stress. We found support for this hypothesis in nine studies ( N total = 16,669) that used survey, archival, and experimental methods, diverse samples, and different operationalizations of cooperative and competitive environments, as well as two kinds of environments that are neither cooperative nor competitive (i.e., independence and unknown interdependence). Studies 1 to 3 found that perceived situational cooperation correlated positively with feelings of autonomy among varsity athletes and employees. Study 3 also provided initial evidence for the proposed mechanisms. To provide causal evidence, Study 4 used an incentivized decision-making task in which we experimentally created cooperative, competitive, and independent situations. Participants felt greater autonomy under cooperative vs. competitive and independent incentive structures. Study 5 found evidence for our hypothesized mechanisms in an experiment conducted in the context of negotiation. Four supplemental studies replicated our experimental findings, extended them to another incentivized decision-making task, and established the causal effect of social threat and stress on autonomy. Overall, our findings underscore the liberating effects of cooperative situations relative to competitive situations and situations that are neither cooperative nor competitive, with consequences for people’s feelings, motivation, and well-being.